International Environmental Law, Fourth Edition - Shelton, Dinah, (International Environmental Law ;, 2025)
Dinah Shelton's International Environmental Law provides a comprehensive and updated analysis of international environmental frameworks, offering insights into the triple planetary crisis-climate change, biodiversity loss, and pollution. This edition further develops the intersection of environmental law with human rights, trade, and other international legal fields, while examining the role of global institutions, treaties, and customary law in addressing today's most pressing environmental issues. The book provides an essential guide to the legal frameworks that underpin efforts to protect the environment and ensure sustainable development in the 21st century.